Challenges facing women living with HIV in Upper Egypt - Abdeldaim, Ahmed Hussein Ali (AUC Knowledge Fountain, 2015)
This research aims to identify challenges that face women living with HIV in Upper Egypt in order to help policy makers and different stakeholders to overcome those challenges. Interviews with women living with HIV from different governorates in Upper Egypt were conducted. In addition, this research included interviews with national AIDS program officials and NGOs managers to obtain different perspectives about the condition of women living with HIV. Women represent half of people living with HIV around the world. The burden of disease on women is even more challenging in many countries due to gender inequality. The effect of culture in Upper Egypt on women living with HIV was an added value to this research as there is shortage in researches that tackled this problem in this particular area in Egypt. Despite efforts to fight HIV in Egypt and to reduce stigma and discrimination, women living with HIV in Upper Egypt face many challenges. What are those challenges and how can Egypt overcome them? Main findings included that women living with HIV in Upper Egypt need a stigma free reproductive health services. They need to disclose about their illness without fear of stigma. Women face many difficulties to access reproductive health services upon disclosure about their status. Women might transfer the virus to their children due to mismanagement of their cases or lack of proper services in health care provision during child birth. Moreover, there is a shortage in the services provided for PLHIV in Upper Egypt including medications’ distributing centers and laboratory tests. Finally, there is a pressing social stigma against PLHIV which results in low utilization of testing services.